Seizure Induced by Defecation in a 15-Year Old Autistic Patient: A Case Report and Literature Review - Shahramian, Iraj; Bazi, Ali; Delaramnasab, Mojtaba (Iranian Journal of Child Neurology, 2020)
Abstract Epilepsy in autism is a relatively common phenomenon. However, reflex seizures provoked by multifactorial stimuli are rare occasions in autistic patients. We reported the first case of defecation induced seizure in a 15 years old girl with autism. The patient had been diagnosed with epilepsy within first year after birth, however, seizures induced by bowel movements were found at the present time in her fifteenth. Reflex seizures showed a tonic pattern that changed to mioclonic represented with one-sided neck deflection. EEG pattern showed abnormal polyspikes and wave during defecation, while the patterns were normal between the attacks. The Patient was responsiveness to adrenocorticotropic hormone therapy with reduced frequency of both reflex and generalized seizures. Although seizure is commonly encountered in autism, reflexed seizures induced by defecation has not been previously reported in this condition.